Creating wealth for poverty reduction in Peru - Vásquez H., Enrique (2006)
The average growth of Peru GDP reached 6 per cent during the 2001-2007 period. However this growth was not in parallel with the microeconomic wellbeing. During this years, the poverty rate decreased 2.7 percentage points in contrast the GDP growth of 27.5 percentage points. As a consequence, searching for high economic growth rates is not enough for reaching a significant decrease of poverty and inequality. In this sense, an effective way might be the promotion of wealth growth initiatives in specific regions with high potential. In order to get a real impact in the poverty reduction it is necessary to change the institutional framework which foster a better environment for the private investment. This article is based on theorical findings and empirical case studies based on local and international experiences. The idea is to suggest ways by which it is possible to link the poor with opportunities in a context of a more inclusive economic growth.